Determinação de compostos bioativos da polpa de muruci (Byrsonima crassifolia (l.) Kunth) obtida por secagem convectiva - CARDOSO, Jéssica Larissa Santa Brigida (2023)
Chronic Noncommunicable Diseases (NCDs) has been increasingly highlighted in the Brazilian epidemiological scenario, associated with high mortality, and the consumption of functional foods is essential to improve this scenario. Objective: To determine the content of bioactive antioxidant compounds in the muruci pulp (Byrsonima crassifolia) obtained by convective drying (in vitro). Materials and methods: Physical-chemical analysis (according to AOAC standards) and bioactive compounds were performed. Results: The sample presented average pH and total titratable acidity of 3.35 ± 0.05 and 2.30 ± 0.25, respectively, low water activity (average of 0.28 ± 0.04) and average of total solubles solids of 14.45 ± 0.45 (ºBrix). Regarding bioactive and antioxidant compounds, an average carotenoid of 325.8 ± 3.55 μg / 100g of βcarotene equivalent to 54.40 ± 1.65 μg / 100g of retinol was found, 118.15 (mg AGE / 100g) of phenolic compounds, 35.2 ± 0.55 (mg / 100g) of flavonoids and 140.3 ± 1.35 (mg / 100g) of vitamin c, demonstrating the role of muruci as a fruit with functional properties.